Suscetibilidade in vitro a antifúngicos, frações de óleos essenciais e modelo experimental de infecção por Malassezia pachydermatis - Schlemmer, Karine Bizzi (2018)
Malassezia pachydermatis is a zoophilic yeast mainly found in the auditory canal of various animal species, and may also be isolated from the skin of humans. Azole and polyene antifungals are the treatment of choice for skin infections, related to Malassezia. However, studies have demonstrated the occurrence of resistance or lower susceptibility of this yeast to some drugs. In this context, the objective of this study was to evaluate the in vitro combination of antifungal agents and antifungals and essential oils fractions (EOs), based on the M27-A3 protocol, with modifications by the checkerboard method. In addition, we sought to evaluate the cytotoxic effects of carvacrol (CRV), cinnamaldehyde (CIN) and thymol (THY) in mouse fibroblasts (3T3 cell line) and to develop an experimental infection model in mice for M. pachydermatis. Combinations of antifungals showed a predominance of indifferent results, with the highest synergism rates for combinations of itraconazole+ caspofungin and clotrimazole+caspofungin (55.17%). Combinations of antifungal and OE fractions showed 80% synergistic interactions for combinations of CRV+nystatin, THY+ nystatin and CRV+miconazole. In cytotoxicity tests using MTT (β- (4,5-dimethylthiazol-2yl) -2,5-diphenyl tetrazoline bromide) CRV and THY were not cytotoxic at most of the concentrations tested (1-50μg/mL ), but CIN reduced cell viability at all concentrations There was a decrease in the concentrations of reactive oxygen species in the presence of CRV, CIN and THY at 24 and 72h, but an increase of 50μg/ml of CIN in 24h of incubation. An increase in DNA fragmentation levels at concentrations of 50 and 100μg/mL of CRV, 25-100μg/mL of CIN and at most THY concentrations was observed. an increase (up to 5%) in apoptosis after exposure to CRV and THY (25-50μg/mL) in 24-72h and an increase in the level of late apoptosis (up to 90%) with CIN (25μg/mL) in 24-72h An infection pattern for M. pachydermatis in Swiss mice immunocompromised with cyclophosphamide (CYP) and acetate hidrocortisone (HCA). This immunosuppressive protocol is already used in several studies to facilitate experimental fungal infections. Previous immunosuppression of the mice allowed infection of the dermis and ear of all animals. In addition, histopathological findings showed yeast, inflammation and hyperkeratosis, confirming otitis and dermatitis by M. pachydermatis. The results of the present study showed some combinations with high percentages of synergism, which allow the elaboration of new treatment hypotheses and point out some candidate combinations to be evaluated in experimental models in vivo.